The Effect of Foreign Direct Investment and Economic Development on Renewable Energy in Indonesia - ., Handri; ., Azib (KnE Social Sciences, 2023)
The study aims to explore the indicators of foreign direct investment (FDI) and their impact on economic development, with a specific focus on renewable energy in Indonesia. It is well-known that FDI plays a significant role in the development of developing countries, and Indonesia, being one of them, still faces challenges in meeting the energy needs of its citizens. The empirical analysis utilizes the Multiple Regression approach with data spanning from 1981 to 2021. The results indicate a cointegration relationship between model parameters and cross-sectional dependence. Additionally, the study finds that FDI and inflation have a negative impact on renewable energy, while population and GDP have a positive and significant effect. Furthermore, economic growth and fossil fuel consumption also positively influence renewable energy consumption. In the long term, the estimation results suggest that FDI and financial development have a simultaneous effect on energy consumption, which aligns with economic growth but not necessarily with renewable energy consumption. This implies that while FDI and financial development contribute to overall energy consumption as the economy grows, they may not directly impact the adoption of renewable energy sources. Based on the research findings, policymakers in Indonesia are encouraged to focus on sustainable development and consider policy transformations that facilitate the transition from fossil fuels to renewable energy sources. Keywords: FDI, GDP, inflation, population, renewable energy, multiple regression